2015
DOI: 10.1088/1758-5090/7/4/045012
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional bioprinting of complex cell laden alginate hydrogel structures

Abstract: Different bioprinting techniques have been used to produce cell-laden alginate hydrogel structures, however these approaches have been limited to 2D or simple three-dimension (3D) structures. In this study, a new extrusion based bioprinting technique was developed to produce more complex alginate hydrogel structures. This was achieved by dividing the alginate hydrogel cross-linking process into three stages: primary calcium ion cross-linking for printability of the gel, secondary calcium cross-linking for rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
219
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(236 citation statements)
references
References 38 publications
6
219
0
2
Order By: Relevance
“…[33,34] The nozzle geometry and the www.advancedsciencenews.com www.advhealthmat.de rheological properties of the applied hydrogel were identified as the most powerful driving forces that determine the level of shear stress in a dispensing system. [35,36] In the present study, we have shown that chemical modification of hydrogels, such as carboxylation, is an effective method to tune the rheological properties of a bioink in order to reduce dispensation associated shear stress-induced cell death. As an alternative to changing the material properties, the printing process can be adjusted to minimize shear stress.…”
Section: −1mentioning
confidence: 87%
See 1 more Smart Citation
“…[33,34] The nozzle geometry and the www.advancedsciencenews.com www.advhealthmat.de rheological properties of the applied hydrogel were identified as the most powerful driving forces that determine the level of shear stress in a dispensing system. [35,36] In the present study, we have shown that chemical modification of hydrogels, such as carboxylation, is an effective method to tune the rheological properties of a bioink in order to reduce dispensation associated shear stress-induced cell death. As an alternative to changing the material properties, the printing process can be adjusted to minimize shear stress.…”
Section: −1mentioning
confidence: 87%
“…This will invariably induce a shear stress, which can be detrimental to the cell viability. [35] The more viscous the solution is, the higher will be the shear stress. Therefore, having a bioink with a low viscosity would be beneficial for techniques that require an extrusion of cell suspension within a biomaterial.…”
Section: −1mentioning
confidence: 99%
“…Mechanically stable alginate scaffolds can be successfully fabricated using CaCl2 solution at higher concentrations (You et al, 2016a), but the incorporated cells can be adversely affected (Cao et al, 2012). Therefore, extruding the alginate precursor into a lower concentration CaCl2 solution has been recommended to limit effects on cell viability (Tabriz et al, 2015). Cellincorporated scaffolds should also be crosslinked immediately after printing to prevent significant decreases in cell viability (Cao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bingham plastic [2], high-density hydrophobic fluorocarbons [5] or more rigid biodegradable materials are used. A novel bioprinting scheme has been developed by Ghanizadeh Tabriz et al [6] wherein 3D cell-laden alginate structures are built up using a three-stage cross-linking process. Partially cross-linked alginate is extruded onto a porous PMMA platform which is lowered into a bath of 100mM calcium chloride solution as each layer is completed thus further cross-linking the structure before finally treating the completed structure with barium chloride in order to extend the degradation time of the hydrogel.…”
Section: Fugitive Support Bathsmentioning
confidence: 99%
“…Bioprinting vascularization can be divided in two groups: bioprinting the actual vessels [55] and bioprinting tissue with nutrient channels [54]. By building up a vessel layer by layer, it is possible to create the intricate structures of hollow, branched blood vessels [6,56] and larger self-supporting structures [57]. Hinton et al [2] showed they can create an entire, full-size, perfusable human right-hand coronary arterial tree out of alginate using FRESH printing.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%